The effects of female age on blood-feeding, insemination, sperm storage, and fertility in the dengue vector mosquito Aedes aegypti (Diptera: Culicidae) (2023)
ABSTRACT:Mating induces behavioral and physiological changes in female insects-collectively referred to as the female post-mating response (PMR)-that facilitate the production of progeny. PMRs are elicited by transfer of male-derived seminal components during mating, but are altered by other factors, including adult age. Increased female age is often accompanied by declines in fertility. However, mating shortly after emergence also impacts fertility in the insect model Drosophila melanogaster. Here, we determined the age post-emergence when females of the vector mosquito Aedes aegypti can be inseminated and blood-feed. We next examined fecundity, fertility, and the storage of sperm in the female reproductive tract in "young" (30-41 hours-old) and "old" (2- and 3-week-old) females, finding that blood-feeding began at 14 hours, and mating at ∼24 hours post-emergence. Although young females consumed smaller blood quantities and stored fewer sperm, they were similarly fertile to 4-day-old controls. Old females, however, suffered significant declines in fecundity by 2 weeks of age. Our results show that female Ae. aegypti start to become sexually receptive 1 day after their emergence, but can ingest blood much sooner, suggesting that mating is not a prerequisite to blood-feeding, and that females can ingest an arbovirus infected blood-meal shortly after emergence.